El rol del acido hilurónico en el metabolismo oxidativo y en los sistemas de señales intracelulares en la capacitacion del espermatozoide criopreservado bovino - Fernández, Silvina (2017)
Hyaluronic acid, a high molecular weight non-sulfated linear glycosaminoglycan, is present in the spermatic reservoir of oviductal epithelium and uterine fluids of ruminants. The main membrane receptor of hyaluronic acid (CD44) is a glycoprotein located in the bovine oviduct, where the binding of hyaluronic acid with its receptor would play a role in oocyte maturation, sperm storage, sperm capacitation and interactions related with fertilization. Heparin is a glycosaminoglycan present in the bovine female genital tract, which is frequently used in this species as a physiological inductor of sperm capacitation in vitro.\nDifferent enzymes are involved in signal transduction during sperm capacitation, including adenylate cyclase, protein kinase A, tyrosine kinase and protein kinase C. In sperm cells the participation of these enzymes has been identified not only in capacitation but also in acrosome reaction and sperm motility. Sperm cells are metabolically active because they possess enzymes necessary to carry out various pathways, such as glycolysis, Krebs cycle and mitochondrial respiratory chain. The objective of these pathways is energy production, since sperm capacitation requires abundant energy for its induction and maintenance. Sperm metabolism is composed of numerous highlighted enzymes in bovine sperm such as lactate dehydrogenase, creatine kinase and isocitrate and malate dehydrogenase of the Krebs cycle.\nReports from other authors and results previously obtained in our laboratory justify the need for further research regarding the role of hyaluronic acid in capacitation, so the aim of the thesis was to determine changes in intracellular signals (membrane adenylate cyclase, tyrosine kinase and protein kinase C), enzyme activities (lactate dehydrogenase, creatine kinase, malate dehydrogenase, isocitrate dehydrogenase) and oxygen consumption using pyruvate and lactate as oxidative substrates in cryopreserved bovine spermatozoa during capacitation with heparin or hyaluronic acid, which could lead to optimize the preparation of the male gamete for bovine oocyte fertilization in vitro.\nIn the present study, the optimal concentration found for hyaluronic acid capacitation and maintenance of sperm viability was 1000 ?g/ml with 60 minutes of incubation. The induction capacitation in cryopreserved bovine sperm by heparin or hyaluronic acid would be involving different intracellular signal mechanisms. These differences would explain why both inducers require different incubation times and concentrations. Although capacitation induced by hyaluronic acid was lower than that registered by heparin, both glycosaminoglycans promoted intracellular changes that allowed true acrosome reaction in vitro induced by lysophosphatidylcholine in bovine sperm.\nOur results suggest that to maintain sperm viability and capacitation the combination of pyruvate and lactate is the best choice to ensure an active metabolism in the gamete. So, with lactate and pyruvate provision in the incubation medium, hyaluronic acid causes a metabolic pattern where the carbon skeletons are used by lactate dehydrogenase, generating lactate, which is not derived to pyruvate to produce energy through Krebs cycle and respiratory chain. Hyaluronic acid maintains a metabolism characterized by the participation of lactate dehydrogenase, creatine kinase, isocitrate and malate dehydrogenase NADP-dependent enzymes to produce enough energy and coenzymes for sperm capacitation. In contrast, heparin capacitation produces a mitochondrial oxidative metabolism, confirmed by the increase in oxygen consumption caused by this inducer together with increased isocitrate and NAD-dependent malate dehydrogenase activities and lower lactate dehydrogenase and creatine kinase activities.\nThe capacitation blocking and the decrease of oxidative metabolism by the presence of membrane adenylate cyclase, protein kinase C and tyrosine kinase inhibitors in sperm samples incubated with heparin suggest that capacitation and oxidative metabolism are modulated by these enzymes. In contrast, the inhibition of membrane adenylate cyclase does not completely block hyaluronic acid induction of capacitation and does not affect mitochondrial oxygen consumption, but decreases lactate dehydrogenase and creatine kinase activities. When protein kinase C and tyrosine kinase were inhibited, hyaluronic acid capacitation proved to be mediated by these enzymes and by isocitrate and NADP-dependent malate dehydrogenase activities. Heparin induced capacitation would be mediated by tyrosine kinase, while hyaluronic acid capacitation induction would involve protein kinase C as well.\nIn conclusion, heparin and hyaluronic acid are two glycosaminoglycans capable to capacitate bovine sperm involving different metabolic pathways and intracellular signals regulation dependent on membrane adenylate cyclase, protein kinase C and tyrosine kinase to obtain fertilizing capacity. This thesis contributes to optimize the conditions of cryopreserved bovine sperm capacitation in vitro, which will impact on in vitro fertilization in this species. Through the increase in the knowledge regarding intracellular mechanisms and changes in sperm metabolism the use of hyaluronic acid as a physiological sperm capacitation inducer is validated.